A Deep Learning Based Approach to Lung Cancer Identification - Cengil, Emine; Cinar, Ahmet (Ieee, 2018)
Cancer is a very common disease type in worldwide. There are many types of cancer. Lung cancer is the most common type of cancer. Lung cancer which is common in both men and women can be fatal. The initiation of treatment by diagnosing cancer is important in reducing the risk of death. In this paper, classification of lung nodules is performs using CT images of SPIE-AAPM-LungX data. Deep learning has been a popular choice for the classification process in recent years. Especially it is used in the implementation of tensorFlow and 3D convolutional neural network architecture from deep learning libraries.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Lung cancer; Deep learning; ResNet; image classification